Unlawful Killing dalam Perspektif Hak Asasi Manusia - Mohamad Firman Aziz; Achmad Irwan Hamzani; Fajar Dian Aryani (SALAM: Jurnal Sosial dan Budaya Syar-i, 2023)
Unlawful killings are extrajudicial killings or court decisions committed by law enforcement officials against people suspected of being involved in a crime. This can be said to be a violation of Human Rights and a serious violation of criminal procedural law. KontraS recorded 52 people dying in the period December 2020 - December 2021 in Indonesia. This study aims to: describe human rights arrangements related to unlawful killing in Indonesia; examines how the theory of Human Rights in the act of extrajudicial killings or unlawful killing. The type of research used is literature, the approach used is normative, data collection techniques use library research, use secondary data sources, and are analyzed using qualitative methods. The results of this study indicate that the authority of law enforcement officials in taking criminal action is carried out based on sufficient initial evidence against the suspect and paying attention to the principles of criminal law, in the act of unlawful killing carried out by law enforcement officials is a violation of human rights.Keywords: Unlawful Killing; Criminal; Ham AbstrakTindakan unlawful killing merupakan pembunuhan di luar proses hukum atau keputusan pengadilan yang dilakukan aparat penegak hukum terhadap orang-orang yang diduga terlibat kejahatan. Hal ini dapat dikatakan pelanggaran Hak Asasi Manusia dan pelanggaran hukum acara pidana yang serius. KontraS mencatat sebanyak 52 orang tewas periode Desember 2020-Desember 2021 di Indonesia. Penelitian ini bertujuan untuk: mendeskripsikan pengaturan hak asasi manusia berkaitan dengan tindakan unlawful killing di Indonesia; mengkaji bagaimana teori Hak Asasi Manusia dalam tindakan pembunuhan di luar hukum atau unlawful killing. Jenis penelitian yang digunakan adalah kepustakaan, pendekatan yang digunakan yaitu normatif, teknik pengumpulan data menggunakan studi kepustakaan, menggunakan sumber data sekunder, dan di analisis dengan menggunakan metode kualitatif. Hasil penelitian ini menunjukkan kewenangan aparat penegak hukum dalam  menindak pidana dilakukan berdasarkan bukti permulaan yang cukup terhadap Tersangka serta memperhatikan asas–asas hukum pidana, dalam tindakan Unlawful killing yang dilakukan oleh Aparat penegak hukum merupakan pelanggaran Hak Asasi Manusia.Kata Kunci: Unlawful Killing; Pidana; Ham